MODIFICATION OF COPOLYMERS BASED ON OLEFIN AND MALEIC ANHYDRIDE AS POUR POINT DEPRESSANT FOR WAXY OILS - S. S. Kozhabekov; A. A. Zhubanov; A. R. Makhmetova; T. B. Abaev (Academic Scientific Journal of Chemistry, 2021)
In this work, we investigated a modification of a copolymer based on α-olefin (octadecene-1) (ODC) and maleic anhydride (MA) synthesized by the method of initiated radical polymerization. In the studies carried out, it was revealed that of all the synthesized copolymers based on maleic anhydride, the copolymer with α-octadecene was the most effective copolymer in reducing the viscosity of oil and TPT. In this work, a copolymer based on maleic anhydride and octadecene-1 (ODC – MA) was modified with primary amines – butylamine (BA), hexylamine (HA), hexadecylamine (HDA), octadecylamine (ODA), benzylamine (BzA). The copolymer was modified in a xylene solution with a Dean – Stark packing; the ratio of the ODC – MA copolymer to amines was 1:1.2 mol. Tololsulfonic acid (TSC) 0.5 wt% was used as a catalyst. Synthesis temperature 140°C, time 8 hours. The degree of completion of the reaction was evaluated by the amount of water formed in the Dean Stark packing. Modified copolymers ODC – MA with amines (ODC – MA – BA, ODC – MA – HA, ODC – MA – HDA, ODC – MA – ODA, ODC – MA – BzA) were characterized by Fourier IR spectroscopy and 1 H and 13C NMR spectroscopy, which indicates the transformation of the original anhydride rings into imide ones. Modified copolymers were tested on waxy oil as depressants. Moreover, all modified copolymers exhibit the properties of depressants – they reduce the viscosity and TPT of oil relative to oil without an PPD. The morphology of waxy crystals formed in oil during a decrease in temperature was determined by microscopy; it was shown that modified waxy crystals of small sizes are formed compared to the original oil without PPDs, which indicates the dispersing effect of modified copolymers based on ODC – MA